Tracking the disseminated sources for compositional work of music theorist-abbot-composer Johannes Nucius - Magdalena Dostálová (Musicologica Brunensia, 2020)
This essay deals with sources for compositional work of music theorist-abbot-composer Johannes Nucius (1556, Görlitz; 25 March 1620, Himmelwitz). Besides a famous theoretical treatise Musices poeticae (1613, Liegnitz) Nucius is also an author of over a hundred sacred vocal compositions and two parodic masses. Even though the motets were published in two printed collections Modulationes sacrae (1591, Prague) and Cantionum sacrarum liber primus and liber secundus (1609, Liegnitz) his compositional output remained slightly neglected. Nevertheless, the tracking and examination of disseminated sources showed, that his music pieces were spread beyond the borders of Upper and Lower Silesia. Given his vivid social relations also outside the monastic life, we should rethink his status of just a music theorist with compositional work of local significance.